Following the drums : African American fife and drum music in Tennessee - Shaw, John M., (John Michael) 1967- (American made music series., 2022)
"Following the Drums: African American Fife and Drum Music in Tennessee is an epic history of a little-known African American instrumental music form. John M. Shaw follows the music from its roots in West Africa and early American militia drumming to its prominence in African American communities during the time of Reconstruction, both as a rallying tool for political militancy and a community music for funerals, picnics, parades, and dances. Carefully documenting the music's early uses for commercial advertising and sports promotion, Shaw follows the strands of the music through the nadir of African American history during post-Reconstruction up to the form's rediscovery by musicologists and music researchers during the blues and folk revival of the late 1960s and early 1970s. Although these researchers documented the music, and there were a handful of public performances of the music at festivals, the story has a sad conclusion. Fife and drum music ultimately died out in Tennessee during the early 1980s. Newspaper articles from the period and interviews with music researchers and participants reawaken this lost expression, and specific band leaders receive the spotlight they so long deserved. Following the Drums is a journey through African American history and Tennessee history, with a fascinating form of music powering the story"--